Produktywność pracy w aspekcie makro- i mikroekonomicznym - Barburski, Jacek; Dobija, Mieczysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The text is aimed at showing the category of productivity in a new perspective and defining its interrelationships with other issues in the domains of enterprise analysis and management. The category of productivity, as defined in the text, is based on the general function of production, which allows to enrich the image of an individuals activities and to better understand the interdependencies between factors that define economic processes. The function covers seven variables, the composition of which expresses better the complexity of the final product with respect to the sum of productive factors. The synthesis of the production function is proceeded by the analysis and selection of variables to be used in the model. The use and implementation of the general production function provides the possibility of measuring the level of management and of identifying the optimum level of remuneration for work. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 25-37